ChemInform Abstract: Conventional and Microwave‐Assisted Synthesis of Benzimidazole Derivatives and Their in vitro Inhibition of Human Cyclooxygenase. Issue 17 (4th April 2013) - Secci, Daniela; Bolasco, Adriana; D'Ascenzio, Melissa; della Sala, Flavio; Yanez, Matilde; Carradori, Simone
Abstract Using a novel microwave‐assisted oxidative cyclization procedure, a large series of benzimidazole derivatives is prepared and evaluated for their ability to inhibit human cyclooxygenases.